Research methods for history - Gunn, Simon, 1954-; Faire, Lucy (Edinburgh University Press, 2016)
Historians have become increasingly sensitive to social and cultural theory since the 1980s, yet the actual methods by which research is carried out in History have been largely taken for granted. Research Methods for History encourages those researching the past to think creatively about the wide range of methods currently in use, to understand how these methods are used and what historical insights they can provide. This updated new edition has been expanded to cover not only sources and methods that are well-established in History, such as archival research, but also those that have developed recently, such as the impact of digital history research. The themes of the different chapters have been selected to reflect new trends in the subject, including landscape studies, material culture and ethics. Every chapter presents new insights and perspectives and will open researchers'minds to the expanding possibilities of historical research
Previous edition: 2012
Keywords: History -- Research.; History -- Methodology.; Histoire -- Recherche.; Histoire -- Méthodologie.; HISTORY -- Study & Teaching.; History -- Methodology; History -- Research